-4-6m-m=2m-4

Simple and best practice solution for -4-6m-m=2m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-6m-m=2m-4 equation:


Simplifying
-4 + -6m + -1m = 2m + -4

Combine like terms: -6m + -1m = -7m
-4 + -7m = 2m + -4

Reorder the terms:
-4 + -7m = -4 + 2m

Add '4' to each side of the equation.
-4 + 4 + -7m = -4 + 4 + 2m

Combine like terms: -4 + 4 = 0
0 + -7m = -4 + 4 + 2m
-7m = -4 + 4 + 2m

Combine like terms: -4 + 4 = 0
-7m = 0 + 2m
-7m = 2m

Solving
-7m = 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
-7m + -2m = 2m + -2m

Combine like terms: -7m + -2m = -9m
-9m = 2m + -2m

Combine like terms: 2m + -2m = 0
-9m = 0

Divide each side by '-9'.
m = 0

Simplifying
m = 0

See similar equations:

| Y=7(x+870) | | 24x+4(x-2)=10(x+2)+8 | | -4(b-3)= | | 1.50h+9.99=36.99 | | Y+24=-14 | | 10+22xn=98 | | 18-4n=6-16m | | 2(4(5)-12)+3(5)= | | 6+x+3=4x+8 | | b+11/17= | | 0=(5x-2)(x+7) | | (2x+4)+X=10 | | -7(7-6k)= | | 60=4(x-2)+5(8x-4) | | 15w-12=3 | | r^2-5r-6=0 | | 9(x+4)+4=-14 | | (08)8+3x=18-2x | | 2(-10y+95)+20y-10=180 | | 3x+2=x+3+2x | | 2(-10y+95)+20y-10=180 | | 3-6y=9-7y | | 9x+150=180 | | x^2-y^2-4y-3=0 | | N+(2n+4)=10 | | 0+7=2+-1 | | 2(x-6)+2x=4(x+8)-44 | | 12x+360=15x+279 | | 5x+2ab=6x-9ab | | 5(x+7)=5x-305 | | x^2+0.1x-0.02=0 | | 22xn=98 |

Equations solver categories